Socio-Economic Background and Access to Internet as Correlates of Students Achievement in Agricultural Science - Adegoke, Sunday Paul (International Journal of Evaluation and Research in Education (IJERE), 2013)
This study investigated access to internet and socio-economic background as correlates of students’ achievement in Agricultural Science among selected Senior Secondary Schools Two Students in Ogbomoso South and North Local Government Areas. The study adopted multi-stage sampling technique. Simple random sampling was used to select thirty (30) students from each of the selected school in the two local governments. Stratified random sampling technique was used to select a sample of 300 students from various strata (school) chosen in the two local governments. Five research questions were answered. Descriptive Statistics, Pearson Moment Correlation and Multiple regressions were used to analyse the data gathered. The study observed that, 67.7% of the students have access to the internet (two-third of the sample). A positive but not significant relationship exists between access to internet and students’ achievement in Agricultural Science (r = 0.110 and p>0.05). There is a positive and significant relationship between socio-economic background and students’ achievement in Agricultural Science (r = 0.515** and p<0.01). Furthermore, relationship between socio-economic background and access to internet is not significant (r = 0.040 and p>0.05). Access to internet and socio-economic background are jointly related to students’ achievement in Agricultural Science. F (3,296) = 37.082, p<0.05, R value of .523ª, R ² of 2.73 and adjusted R square of .266.